BAGIR MANAN HUKUMNYA WAJIB ATAU TIDAK WAJIB HADIR JIKA DIPANGGIL - Didik Endro Purwoleksono (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
There are five parameters that a judge should consider to make a verdict in a criminal case. As stated in Ps. 184 KUHP the parameters included (1) the witness ’ testimony (2) the statement of expert witness, (3) letters or documents, (4) clues, and (5) the statement of the defendant. Someone that is invited as a witness has the obligation to attend the trial. The absence in a trial without any valid reason can be sued according to Ps. 216 jo 224 KUHP.